2019
DOI: 10.3390/md17090501
|View full text |Cite
|
Sign up to set email alerts
|

Echinochrome A Attenuates Cerebral Ischemic Injury through Regulation of Cell Survival after Middle Cerebral Artery Occlusion in Rat

Abstract: Of late, researchers have taken interest in alternative medicines for the treatment of brain ischemic stroke, where full recovery is rarely seen despite advanced medical technologies. Due to its antioxidant activity, Echinochrome A (Ech A), a natural compound found in sea urchins, has acquired attention as an alternative clinical trial source for the treatment of ischemic stroke. The current study demonstrates considerable potential of Ech A as a medication for cerebral ischemic injury. To confirm the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
(34 reference statements)
0
15
0
Order By: Relevance
“…All parts of these organisms have been used in traditional medicine [ 121 ] and are a highly valuable source of medicines. The sodium salt of naphthoquinone pigment echinochrome A ( 17 ) (under the name of histochrome), isolated from the shell of sea urchin Scaphechinus mirabilis , is approved in Russia for the treatment of acute myocardial infarction and, in ophthalmology, for dystrophic diseases of the retina and cornea [ 9 , 122 , 123 ]. The absorption of histochrome was studied in rabbits after subconjunctival and parabulbar injection.…”
Section: Pharmacokinetics Studies In Animalsmentioning
confidence: 99%
“…All parts of these organisms have been used in traditional medicine [ 121 ] and are a highly valuable source of medicines. The sodium salt of naphthoquinone pigment echinochrome A ( 17 ) (under the name of histochrome), isolated from the shell of sea urchin Scaphechinus mirabilis , is approved in Russia for the treatment of acute myocardial infarction and, in ophthalmology, for dystrophic diseases of the retina and cornea [ 9 , 122 , 123 ]. The absorption of histochrome was studied in rabbits after subconjunctival and parabulbar injection.…”
Section: Pharmacokinetics Studies In Animalsmentioning
confidence: 99%
“…Studies have evaluated the neuroprotective effect of Ech A in animal models of hemorrhagic or ischemic stroke [ 48 , 49 , 50 , 51 ]. Histochrome (0.7 mg/kg, bolus intraperitoneal injection) effectively reduced the edema caused by hemorrhage, which thus alleviated neurological symptoms in rats [ 48 , 51 ].…”
Section: Clinical Application and Target Molecules Of Ech Amentioning
confidence: 99%
“…It altered the expression levels of cell viability-related factors. It was concluded that the protective role of this natural compound against cell death is connected with its antioxidant effect [11].…”
Section: Ofmentioning
confidence: 99%